8+6h=5h-6

Simple and best practice solution for 8+6h=5h-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+6h=5h-6 equation:



8+6h=5h-6
We move all terms to the left:
8+6h-(5h-6)=0
We get rid of parentheses
6h-5h+6+8=0
We add all the numbers together, and all the variables
h+14=0
We move all terms containing h to the left, all other terms to the right
h=-14

You can always share this solution

See similar equations:

| -18+12m-17m=18-3m | | -14.9m+10.12=-14m+19.84 | | -8=-7+x/9 | | x+2/4=x+1/7 | | 13+19z=9+15z | | 7x-1=-3x=5 | | 3r=-8+5r | | 16-6c=-4c | | -20-9d-20=-3D+20 | | 7x/18=5/9+-8x/4 | | 7x-1=3xx=5 | | -17t-16=-16t+3 | | x+7/18=5/9+x-8/4 | | 2k-3k-10=10-3k | | -6g-9=-5g | | 1-2b=-4b+10+3b | | -9+v=7v+9 | | -10-6k=-8k+10 | | 1.2+z=3.2 | | 4(x-3)+20=3(x=4) | | -9+9q=1+10q | | -12+x/2=2 | | -6m=-3m-9 | | -7-9p=-10p | | 7x=-51+9 | | 2j+9=-j | | X(3.44)+x(4.33)=49.29 | | 9-4t=-3t | | x-7.5=16.4 | | m?5=180°-81°=99° | | -1.3x+7=31 | | 0.04x=0.01 |

Equations solver categories